Private investment and public policy in Egypt, 1960-1986 - Shafik, N; Shafik, Nemat T. (1989)
﻿ The determinants of private investment and the role of government policy in Egypt are analyzed with a focus on the debate over "crowding out" versus "crowding in," the implications of administered interest rates, and the consequences of uncertainty. A theoretical model of investment is developed that integrates the microfoundations of firm decision making with the determinants of investment at the macroeconomic level. The model, which draws on case studies of fifty private firms in Egypt, is characterized by oligopolistic markets, putty-clay technology, credit rationing, and rigidities in the supply of capital goods. Econometric testing of the model uses the recent literature on cointegration and error correction to address the problem of spurious correlations while retaining long run information about the equilibrium relationship between aggregate investment and its determinants. The empirical evidence shows that the investment decision depends on expected profits which are a function of demand, costs and mark ups. The impact of government policy on private capital formation operates through these determinants, such as the positive effects of protection or restrictive licensing on private sector mark ups. Using the model to analyze the oil boom of the 1970s, it is possible to explain the sectoral distribution of private investment, which diverged from the predictions of conventional Dutch disease theory about the consequences of a trade shock. The findings indicate that the sharp rise in the private investment ratio during the 1970s in Egypt stemmed more from the consequences of the foreign exchange windfall on demand, costs, and mark ups than from the effect of fiscal incentives introduced by the state. However, government policy was crucial in determining the structure of incentives in the economy which favoured capital intensive, heavily indebted, import substituting investments in protected sectors. The private sector responded to this incentive structure by concentrating on those activities where economic rents were highest.